Relating the philosophy and practice of ecological economics: the role of concepts, models, and case studies in inter- and transdisciplinary sustainability research - Stefan Baumgärtner; Christian Becker; Karin Frank; Birgit Müller; Martin Quaas (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
We develop a comprehensive multi-level approach to ecological economics (CML-approach) which integrates philosophical considerations on the foundations of ecological economics with an adequate operationalization. We argue that the subject matter and aims of ecological economics require a specific combination of inter- and transdisciplinary research, and discuss the epistemological position on which this approach is based. In accordance with this understanding of inter- and transdisciplinarity and the underlying epistemological position, we develop an operationalization which comprises simultaneous analysis on three levels of abstraction: concepts, models and case studies. We explain these levels in detail, and, in particular, deduce our way of generic modeling in this context. Finally, we illustrate the CML-approach and demonstrate its fruitfulness by the example of the sustainable management of semi-arid rangelands.
Keywords: 330; Umweltökonomik; Nachhaltige Entwicklung; Interdisziplinäre Forschung; Erkenntnistheorie